Ministerial decree 87/2016 regarding the non enforcement of the export rules on certain raw materials exported to the free zones = قرار وزاري رقم 87 لسنة 2016 في شأن عدم سريان القواعد التصديرية على بعض الخامات المصدرة للمناطق الحرة - Egypt. Ministry of trade and industry. The Egyptian Customs Authority (2025)
Ministry of Trade and Industry decree no. 87 of the year 2016 regarding the non-enforcement of the export rules on certain raw materials exported to the free zones وزارة التجارة والصناعة قرار رقم 87 لسنة 2016 فى شأن عدم سريان القواعد التصديرية على بعض الخامات المصدرة الى المناطق الحرة